A case report of a long-term survivor after inadvertent ligation of the left pulmonary artery during intended ductal ligation. Issue 4 (22nd March 2022) - Zeng, Qi-xian; Liu, Zhihong; Xi, Qun-Ying; Xiong, Changming
Abstract: Background: Patent ductus arteriosus (PDA) can close on its own during childhood. Patent ductus arteriosus with left pulmonary artery (LPA) occlusion is rare. Here, we describe possible aetiologies of this condition and treatment strategies based on recent guidelines. Case summary: A 35-year-old man experienced shortness of breath for 20 years. Physical examination revealed pitting oedema, digital clubbing, and bi-phasic murmur along the left sternal border at the 2nd and 3rd intercostal space. Congenital heart disease was suspected. Echocardiography revealed a severely dilated pulmonary trunk and PDA; however, the LPA was not visible. The patient has undergone PDA ligation surgery >30 years ago, which may have caused accidental LPA ligation; however, extreme elevation of pulmonary pressure led to increased difficulties in performing LPA reconstruction and PDA division. Therefore, pulmonary arterial hypertension (PAH) initial combination therapy with parenteral prostanoids was prescribed. The patient's condition improved gradually. Discussion: Inadvertent ligation of the LPA instead of PDA is a rare and usually fatal complication during ductal ligation. Patients who survive this catastrophic complication usually develop the progressive pulmonary vascular disease with increased pulmonary pressure and impaired lung parenchyma resulting in right heart and respiratory failure. Early and regular follow-up with cardiac imaging studies is important to diagnose this complication. Reconstruction of the ligated LPA and PDA late in the disease course is difficult due to the development of pulmonary arterial hypertension. Initial PAH combination therapy may be valuable for relieving the patients' symptoms at that stage. Heart and lung transplantation can also be considered in suitable patients.